Clinical evolution of perinatal pathology. Dialogues with the Teacher - E. A. Morozova (Эпилепсия и пароксизмальные состояния, 2021)
Here are reported the data of investigating clinical evolution of perinatal brain pathology performed under the auspices of Professor V.A. Karlov. Analysis of the data obtained revealed an importance for detecting ante- and intranatal predictors for most relevant neurological disorders in childhood: neonatal seizures, some epilepsy forms, headache and attention deficit / hyperactivity disorders. The speaker argues for the necessity to conduct topical diagnostics of the nervous system disturbances in neonates and justifies a relationship between early and delayed neurological disorders in diverse pediatric periods.